The working alliance inventory – short version: psychometric properties of the patient and therapist form in youth mental health and addiction care - Patty van Benthem; R. M. van der Lans; A. Lamers; P. Blanken; R. Spijkerman; R. R.J.M. Vermeiren; V. M. Hendriks (BMC Psychology, 2024)
Abstract The therapeutic alliance is considered to play an important role in youth treatment. The commonly used versions of the Working Alliance Inventory (WAI) are based on Bordin’s three-dimensional alliance model. However, previous psychometric studies of the WAI did not find this three-dimensional structure in youth psychotherapy. These earlier findings may indicate different perceptions of the alliance by adolescent versus adult patients, but may also be due to methodological shortcomings. The current study aims to address previous study limitations by evaluating the factor structure of the short version of the WAI (WAI-S) in youth treatment in multilevel analysis to address the hierarchical structure of the alliance data. We examined the psychometric properties of the patient (n = 203) and therapist (n = 62) versions of the WAI-S in youth mental health and addiction care and tested four multilevel models of alliance at start of treatment and 2-month follow-up. Our results suggests a two-factor model for youth and a three-dimensional model for their therapist at both time points. Since this is the first study that finds a best fit for a two-dimensional construct of alliance in youth, more research is needed to clarify whether the differences in alliance dimensions are due to measurement differences between the WAI-S for youth and therapists or whether youth and their therapists truly differ in their perceptions of the concept of alliance.